Induksi Akar Anggrek Dendrobium lasianthera dengan Pemberian Beberapa Konsentrasi Naphthalene Acetic Acid (NAA) Secara In Vitro - Arli, Naura Muthiah; Noli, Zozy Aneloi (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Dendrobium lasinthera is an orchid that has considerable potential as a raw material for anti-cancer drugs and for the production of cut flowers. Therefore, this orchid is a plant with high economic value. This orchid has beautiful and long-lasting flowers. The demand for this orchid is increasing along with its diverse uses, so the propagation of this orchid needs to be increased. In vitro propagation is the most appropriate step to reproduce this orchid. One of the stages that determines the success of orchid propagation through tissue culture is the root induction stage before acclimatization. Using the right type and concentration of Growth Regulatory Substances (ZPT) is very important. This research aims to determine the effect of several NAA Growth Regulatory Substance (ZPT) concentrations and determine the best NAA concentration for Dendrobium lasianthera root induction. This study used a Completely Randomized Design (CRD) with several NAA concentrations (Control (A); 0.5 mg/L (B), 1 mg/L (C), and 1.5 mg/L (D)), on Murashige & Skoog (MS) media. The results of this study show that NAA has a significant influence on the percentage of root formation, root emergence time, and root length in the Dendrobium lasianthera orchid. NAA 1.5 mg/L is the best concentration for induction of Dendrobium lasianthera orchid roots.